2014
DOI: 10.4315/0362-028x.jfp-13-049
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Salmonella Serovars, Listeria monocytogenes, and Escherichia coli O157:H7 in Mediterranean Ready-to-Eat Meat Products in Jordan

Abstract: The presence of Salmonella, Listeria monocytogenes, and Escherichia coli O157:H7 in ready-to-eat (RTE) meat products is considered a major concern for food control authorities worldwide. The aims of this study were to determine (i) the prevalence of Salmonella, L. monocytogenes, and E. coli O157:H7 in Mediterranean RTE chicken and beef (CB) products sold in Jordanian restaurants and (ii) the susceptibility of the isolates to antibiotics. A total of 1,028 samples of various types of RTE CB products (550 RTE chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 31 publications
(31 reference statements)
2
17
1
1
Order By: Relevance
“…In a related study, lower incidence (0.8%) of Salmonella spp. in RTE chicken products was obtained by Osaili et al (2014). Diaz-Lopez et al…”
Section: Resultsmentioning
confidence: 99%
“…In a related study, lower incidence (0.8%) of Salmonella spp. in RTE chicken products was obtained by Osaili et al (2014). Diaz-Lopez et al…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the presence of multidrug-resistant E. coli to B-lactams groups is attributable to the acquired ability of the strains to produce Blactamase, which hydrolyzes B-lactams ring, rendering the entire compound inactive. Osaili et al (2014) reported that most Salmonella isolates were resistant to the majority of antibiotics tested. Harakeh et al (2005) also found that 86 and 57% of the Salmonella isolates from meat-based fast food in Lebanon were resistant to trimethoprim-sulfamethoxazole and gentamicin, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This detection rate of Salmonella -positive samples is close to the 57.5% of street-vended foods ( n = 40) in Ethiopia (Mulugeta and Million, 2013), yet it is much higher than the 41.0% of RTE meats ( n = 79) in Taiwan (Manguiat and Fang, 2013), and the 40.0% of RTE meats ( n = 20) in Havana, Namibia (Shiningeni et al, 2018). On the other hand, other studies have reported extremely low detection rates of Salmonella -positive samples (<4.0%) in RTE meat products (Osaili et al, 2014; Yang et al, 2016; Yang et al, 2018). Together these results indicated that Salmonella in RTE meat products throughout the world was more prevalent in specific years tested.…”
Section: Discussionmentioning
confidence: 84%